Perancangan Sistem Pendukung Keputusan Rekomendasi Bimbingan Belajar Bagi Siswa Sekolah Dasar Menggunakan Metode SAW di MI Al Muhajirin - Ardiansyah; Dimas Abisono Punkastyo (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
The assessment of students’ tutoring needs at MI Al Muhajirin is still conducted manually based on teachers’ observations, which may lead to subjective and unstructured evaluations. This study aims to develop a web-based Decision Support System (DSS) to classify students’ tutoring needs objectively and systematically. The method applied in this research is Simple Additive Weighting (SAW), with the system development carried out using the Extreme Programming (XP) approach and tested through Black Box Testing and White Box Testing. The system was developed using the PHP programming language and a MySQL database. The results indicate that the system is capable of processing student data based on multiple assessment criteria and generating preference values along with tutoring recommendation classifications in a structured manner. The implementation of this system assists teachers in making more objective, consistent, and transparent decisions, while also facilitating systematic documentation of assessment results to support evaluation processes and communication with schools and parents.